Boronizing for Electro-Metallurgical Tungsten Carbide/Steel Composite - Li, Ping; Liu, Ning; Liu, Aijun; Deng, Huangbin (Asian Journal of Chemistry, 2014)
The paper studies the electro-slag melting and casting tungsten carbide/steel composites, first the sample is quenched and tempered, then boronizing treatment is performed by solid powder method and microstructure and mechanical property of boronizing samples by different temperature are compared. The results show that, by XRD the composition of samples are founded, including FeB, Fe2B2, CoB and Ni3B. It is found that properties of sample are the best at 950 ºC for 7 h boronizing. After boronizing treatment, Vickers hardness at surface of samples is 50 % higher than samples which quenched and tempered only and 100 % higher than original samples.